Pendampingan Mewujudkan Kesadaran Wajib Pajak Bagi Penggiat UMKM Desa Gede Pangrango Kecamatan Kadudampit, Sukabumi - Ni Putu Eka Widiastuti; Wiwi Idawati; Indah Masri; Susilawati Susilawati; Tutty Nuryati; Uswatun Khasanah; Saprudin Saprudin; Randy Kuswanto; Muhammad Adrian Muluk; Budi Kurniawan (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2025)
This community service project conducted by the Jakarta area accounting lecturer forum team aims to increase tax awareness among Micro, Small, and Medium Enterprise (MSME) owners in the Gede Pangrango Tourism Village. The project conducted workshops, provided individual tax assistance, and advocated for policy changes. As a result, there is potential for a significant increase in tax awareness, improved tax compliance, and increased tax revenue following these activities. The project successfully established a sustainable tax education program for MSME owners in Gede Pangrango Village with several contributions, including: (1) increased tax knowledge and compliance; (2) empowerment of MSMEs; (3) improved quality of financial statements; (4) increased competitiveness of MSMEs, and (5) appreciation from the local government for the role of academics in assisting MSME owners to understand tax obligations.